Ventricular Myocardial Sheet - Ali, Mostafa R. (AL-Kindy College Medical Journal, 2018)
Background: Despite the fact that the exact architecture and orientation of ventricular myocardium are critical to cardiac functions either in health or disease, it is still debated.Objectives: Anatomical demonstration of the ventricle myocardium (VM)as a single, long and continuous muscular sheet and this muscular sheet can be dived into 3-segments. As a new anatomical concept the left ventricle is a triple layers wall; whether the right ventricle is a single layer wall.Histological demonstration of different directions of muscle-fibers at each layer of ventricular myocardium.Type of the study: Cross- sectional study.Methods: In this study 100-heart (fish, chicken, goat, sheep and cow) were dissected and analyzed. Dental lacrona and wax knife used majorly in the dissection, boiling of the hearts with distilled water and finally opening them by the “opening-technique”.Results: Ventricular myocardium is a single, long and continuous muscular sheet in 100-samples of different species which had been included in the study (passing from the fish toward the cow). VMS can be divided into 3-segments in (100% of cow, 95% of goat and 85% of sheep). The left ventricle is a triple layers wall; whether the right ventricle is single layer wall, this result observed in (100% of cow, 95% of goat and 85% of sheep).Finally different directions of muscle fibers observed at each layer of ventricular myocardium where the subendocardial layer shows transverse running pattern of muscle fibers, mesocardial layer shows longitudinal running pattern of muscle fibers and subepicardial layer shows mixed running patterns of muscle fibers.Conclusion: Ventricular myocardium is single, long and continuous muscular sheet. This sheet consists of 3-segments. These segments coils in spiral track and form the triple layers left ventricular wall and the single layer right ventricular wall. By histological examination of ventricular myocardial layers different directions of muscle fibers observed at each layer.